A Year on the Rock: A Methods Professor Returns to the Classroom - Bradley J. Burenheide (Educational Considerations, 2018)
As a Methods Professor in a Research I institution in the Midwest and the largest education program in its respective state, I faced a crisis after ten years in higher education. The concern I faced was whether or not the repertoire I taught my students was appropriate and meaningful in their training. While staying abreast of current research and strategies, I wanted to ensure that my techniques were still applicable to working with students after ten years of less connection with classrooms. This article discusses the framework employed in the research experience as well as the big lessons that were gleaned from two years teaching in a high school.
Keywords: Social Studies; Methods; Pedagogy; Professor